Influence of ICT and Its Dynamic Change in Daily Life of Human Being - SHARMA, DR. MEENAKSHI (The journal of contemporary issues in business and government, 2021)
In modern world, new emerging technologies are emerging on daily basis. As the technologies are increasing day by day, human is getting more and more dependent of it. ICT is one of the most advanced technology that is being used by millions of people worldwide. In this research work, impact of ICT, and its role in our daily life in different sectors has been studied in brief. A methodology is presented about how ICT works in online banking android application as these days, online payments is trending and widely used by millions of people to avoid cash payments during Covid-19 pandemic. In upcoming time, ICT will reduce 70% of the human efforts and automatic work done will be the new trend in many sectors such as education sector, daily life, administration, health care and hospitality etc. from future perspective this research work may help learners to better understand the facts about ICT.